Distribution and dispersal of metals in contaminated fibrous sediments of industrial origin. (January 2019) - Apler, Anna; Snowball, Ian; Frogner-Kockum, Paul; Josefsson, Sarah
Abstract: Industrial emissions can impact aquatic environments and unregulated discharges from pulp and paper factories have resulted in deposits of cellulose fiber along the Swedish coast. These deposits are contaminated by metals, but due to their unique fibrous character the extent of sorption and dispersal of the metals is unclear. Fibrous sediments were sampled at two sites in the Ångermanälven river estuary, Sweden. The partitioning of metals between the sediment, pore water and bottom water was investigated and the degree of bioavailability was evaluated. The levels of metals in the sediment were high in fibrous or offshore samples, depending on the metal, whereas the levels of dissolved metals in pore water were low or below the limit of quantification. Partition coefficients ( K D ) showed that sorption to the sediment was stronger at one of the fibrous sites, possibly related to the type and size of organic matter. Undisturbed bottom water samples contained low levels of both dissolved and particle bound metals, but when comparing measured metal concentrations to threshold values of ecological status and ecotoxicological assessment criteria, both sediments and bottom water may be detrimental to living organisms. In-situ re-suspension experiments showed that the concentrations of particle bound metals increased whereas the dissolved concentrations decreased. The analyzed metals are probably retained by the solid phases of the fibrous sediment or adsorbed to particles in the water, reducing their bioavailability. Highlights: Old pulp industry waste contaminated by metals is present in coastal sediments. Levels of some metals are harmful (exceed thresholds) in sediment and bottom water. Pore/bottom water levels of metals do not visibly reflect sediment levels. Geochemical conditions in the sediment, e.g. hypoxia, is likely to affect sorption. Dissolved metal levels in bottom water did not increase after sediment resuspension.